1986
DOI: 10.1017/s0031182000064088
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the glutamate dehydrogenase ofPlasmodium falciparum

Abstract: SUMMARYPolyclonal antisera raised against Plasmodium, knowlesi reacted with (1) NADP-specific glutamate dehydrogenase (GLDH) of P. knowlesi, (2) GLDH of P. falciparum and (3) GLDH of Proteus spp. The antisera did not react with NAD(P) GLDH from bovine liver. Polyclonal antisera raised against the GLDH of Proteus spp. cross-reacted with GLDH from P. falciparum. Monoclonal antibodies (McAbs) obtained from mice immunized with Proteus GLDH were either specific for the bacterial enzyme or cross-reacted with P. falc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A previous study, using cross-reacting antibodies, suggested that the parasites possess a cytosolic GDH protein without distinguishing which of the three GDH proteins is detected by the antibodies [52]. It was demonstrated here that GDHa-GFP, expressed episomally in P. falciparum , localizes exclusively to the parasite's cytosol while there is no GFP fluorescence present in the mitochondrion or the apicoplast.…”
Section: Discussionmentioning
confidence: 63%
“…A previous study, using cross-reacting antibodies, suggested that the parasites possess a cytosolic GDH protein without distinguishing which of the three GDH proteins is detected by the antibodies [52]. It was demonstrated here that GDHa-GFP, expressed episomally in P. falciparum , localizes exclusively to the parasite's cytosol while there is no GFP fluorescence present in the mitochondrion or the apicoplast.…”
Section: Discussionmentioning
confidence: 63%
“…fakiparum glutamate dehydrogenase. In spite of its relative abundance and its physiological importance (Walter et al, 1974), enzymically active plasmodia] GDH has not been purified to homogeneity before; the isolation of this protein as an antigen was achieved in the elegant study of Ling et al (1986). Since we were primarily interested in GDH only as a stable marker enzyme of the parasite compartment, the enzyme was not studied in detail; some basic enzyme kinetic data of purified P. ,falciparum GDH are, however, summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…All data rcfer to the pH optima o f 8.0 and 7.0, respectively. V for the reverse reaction was 22 U/mg (see Table 1 (Ling et al, 1986;Vander Jagt et al, 1989). The remarkable heat stability of the enzyme has been mentioned in khe previous section.…”
Section: Resultsmentioning
confidence: 99%
“…Our results, obtained under reducing conditions, led to the interpretation that native GDH(NADP + ) could correspond to a protein consisting of 4 subunits. GDH (NADP + ) shows no cross-reaction with the enzyme of mammals (14), but rather with Proteus spp.…”
Section: Discussionmentioning
confidence: 99%